2014
DOI: 10.1111/ijcs.12081
|View full text |Cite
|
Sign up to set email alerts
|

Applying neutralization theory to fair trade buying behaviour

Abstract: More and more consumers are willing to pay a premium for fair trade products. However, great potential remains as the market shares of these products are still low. In the present study, neutralization theory was applied to investigate the reasons for consumers hesitating to buy more fair trade products. A postal paper-and-pencil survey was sent out using random addresses from the telephone book in the German-speaking part of Switzerland, resulting in a final sample size of n = 620. The results show that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
(59 reference statements)
1
38
0
Order By: Relevance
“…While acknowledging that the best option is available, people can neutralize their deviant behavior by claiming that the circumstances do not offer more realistic options thereby asking too much of them (Rosenbaum, Kuntze, and Wooldridge 2011). For example, Brunner (2014) found that consumers neutralized their failure to buy fair trade products by claiming that these products are too expensive and there are no cheaper alternative fair trade products. In this regard, people can also argue that because the circumstances are bad, it is unrealistic for them to behave well.…”
Section: Blaming the Limited Optionsmentioning
confidence: 99%
“…While acknowledging that the best option is available, people can neutralize their deviant behavior by claiming that the circumstances do not offer more realistic options thereby asking too much of them (Rosenbaum, Kuntze, and Wooldridge 2011). For example, Brunner (2014) found that consumers neutralized their failure to buy fair trade products by claiming that these products are too expensive and there are no cheaper alternative fair trade products. In this regard, people can also argue that because the circumstances are bad, it is unrealistic for them to behave well.…”
Section: Blaming the Limited Optionsmentioning
confidence: 99%
“…Presumably, this may root in a biased cognitive evaluation (e.g., disgrading) on the efficiency of individual efforts. Brunner (2014) terms this phenomenon as denial of benefits (of personal efforts). Feelings of helplessness may develop when people believe in that the environmental problem is intractable due to its severity (Pelletier et al, 1999), it is too late to do anything, and the damage is irreversible by human action (Lorenzoni et al, 2007) or other consumers wouldn't follow suit, so one can change nothing alone (Gifford, 2011;Lorenzoni et al, 2007).…”
Section: Denial Of Personal Effectivenessmentioning
confidence: 99%
“…In return, the consumer pays a surcharge for the product (Koppel and Schulze, 2013). Likewise, a growing number of consumers are prepared to pay higher prices for fair trade, but the percentage remains scant (Koppel and Schulze, 2013;Brunner, 2014). It remains established that social and environmental sustainability stand as two clearly separate factors within a mutual dependency (Huvstedt and Bernard, 2010).…”
Section: Salient Product Attributes Regarding Sustainable Food Consummentioning
confidence: 99%
“…It remains established that social and environmental sustainability stand as two clearly separate factors within a mutual dependency (Huvstedt and Bernard, 2010). Above all, a partiality for fair trade is most likely to the group of younger, politically liberal women who have an aboveaverage education (Brunner, 2014;Taylor and Boasson, 2014).…”
Section: Salient Product Attributes Regarding Sustainable Food Consummentioning
confidence: 99%
See 1 more Smart Citation